2020
DOI: 10.5534/wjmh.190092
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results after Surgical Treatment of Congenital Penile Curvature Using a Modified Nesbit Technique

Abstract: Purpose: Congenital penile curvature (CPC) is a rare condition with surgical correction being the standard therapy. In the current study, we report long-term results analyzing the surgical and functional outcomes using a modified Nesbit technique. Materials and Methods: Patients with CPC were included. After penile degloving and mobilization of the neurovascular bundle an artificial erection was performed. An ellipsoid part of the tunica albuginea was excised at the point of maximum curvature on the convex sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…Post-operative penile shortening is the most frequent complication of every plication and Nesbit procedures. In our study, the mean length loss was of 0.83±0.79 cm, in accordance to what was previously reported (35). Different to a previous study (36), penile shortening was not significantly associated to direction and degree of curvature.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Post-operative penile shortening is the most frequent complication of every plication and Nesbit procedures. In our study, the mean length loss was of 0.83±0.79 cm, in accordance to what was previously reported (35). Different to a previous study (36), penile shortening was not significantly associated to direction and degree of curvature.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, satisfaction rate in our patients was slightly lower compared to the data described by Rolle (91.4% vs. 94%), probably because we treated also curvatures >60°. Moreover, in some studies erectile function raised up after surgery without reaching statistical significance, probably for the use of tourniquet during the technique and the prolonged time of penile ischemia (34,35). Rolle and colleagues did not consider the advantages of the penile clampless, probably because there was no scientific demonstration of the penile damage after a long period of ischemia at the time of the study (14).…”
Section: Discussionmentioning
confidence: 99%
“…Penile curvature is a congenital or acquired deformity which results in sexually debilitating condition and significant psychological stress for patients and their partners (15). Once medical treatment is excluded or unuseful, surgery becomes the standard of choice (16). Both shortening and lengthening procedures are good options for patients.…”
Section: Discussionmentioning
confidence: 99%
“…All studies demonstrated that the plication techniques for residual curvature during PPI seem to be safe and effective in patients with mild to moderate penile curvature. No article reported a classic or modified Nesbit technique (48). Still, the plication technique has always the risk of damaging the implant during suturing.…”
Section: Plication Techniquesmentioning
confidence: 99%